The effect of nano-chitosan and as mouthwash and denture cleanser: In vitro study - Sabreen Waleed Ibrahim; Farah Nabeel Mohammed Tahir AlKhayyat; Maha Jamal Abbas (Journal of Applied Biomaterials & Functional Materials)
Introduction: Besides mechanical cleaning, mouthwashes, and denture cleansers are typical supplements for oral care. Many chemical mouthwashes and denture cleansers provide positive effects, but finding safe and natural alternatives should be the priority. Aim of study: This study aims to investigate the effectiveness of natural materials as mouthwash and denture cleansers. Material and method: In examining the antimicrobial efficacy of mouthwashes, the minimum inhibitory concentration values were determined for five groups: distilled water (negative control), 0.2% chlorhexidine, chitosan solution, Saussurea costus solution, and chitosan-Saussurea solution. As for denture cleansers, the efficacy was evaluated after immersing polymethylmethacrylate (PMMA) disks in the previous solutions. The cell viability of Human Gingival Fibroblast (hGFs) after treatment with tested solutions was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. Data was analyzed using ANOVA with Bonferroni post hoc tests. Result: The prepared solutions showed comparable antimicrobial efficacy and cell viability as chlorohexidine. The chitosan- Saussurea costus solution demonstrated a higher antimicrobial effect and better prevention of microorganisms’ adherence to PMMA disks and cell viability. It also did not affect the roughness of PMMA in the short term. Conclusion: The new denture cleaning and mouthwash agent, which contains the natural constituents of chitosan and Saussurea costus , demonstrates significant antibacterial effectiveness and serves as a viable eco-friendly alternative to commercial mouthwash, as well as exerting minimal influence on denture roughness. Clinical implications: Chitosan and Saussurea costus have antibacterial and anti-inflammatory properties that can potentially enhance oral health. These materials present a viable path toward the production of safe, efficient, and sustainable oral care products due to their natural and biocompatible substitutes.